A comparative study of fine-needle aspiration cytology and histopathology in salivary gland lesions - Vaidya, S; Sinha, A; Narayan, S; Adhikari, S; Sabira, KC (Journal of Pathology of Nepal, 2011)
Background: A wide variety of benign and malignant tumours originate in the salivary glands and insufficient tumour cells make their diagnosis difficult in some patients. The aim of this study was to evaluate the efficacy of fine-needle aspiration cytology in the diagnosis of salivary gland lesions and to correlate cytological findings with histopathology. Materials and Methods: This was a prospective study done from September 2002 to May 2004. Fine needle aspiration cytology was performed in 58 patients with clinically significant salivary gland masses. Results: Fine needle aspiration cytology categorized 67.24% of the salivary gland lesions as neoplastic and 32.76% as non-neoplastic lesions. Amongst the neoplastic lesions, 76.9% were benign and 23.1% were malignant cases. Histopathological examination revealed that 81.05% of the cases were benign and 18.95% were malignant. Fine needle aspiration cytology had a sensitivity, specificity and diagnostic accuracy of 81.82%, 100% and 96.55%, respectively. The positive predictive value and negative predictive value was 100% and 95.9%, respectively. Conclusion: Fine needle aspiration of the salivary gland is a safe and reliable technique in the primary diagnosis of salivary gland lesions. Although, limitations are encountered while predicting specific lesions on cytology, especially when dealing with cystic and some malignant lesions, this study has shown that fine needle aspiration cytology has a high sensitivity, specificity and diagnostic accuracy in diagnosing salivary gland lesions. Keywords: Salivary glands; Fine needle aspiration cytology; Histopathology DOI: http://dx.doi.org/10.3126/jpn.v1i2.5403 JPN 2011; 1(2): 108-113